Time trends in lung cancer incidence by histology in South Australia: likely causes and public health implications - Anh‐Minh Nguyen; Colin G. Luke; David Roder (Elsevier, 2003)
Abstract Objectives: In response to reported increases in ratios of adenocarcinomas to squamous cell carcinomas of the lung in other populations, to investigate and consider public health and clinical implications of time trends in lung cancer incidence by histological type in South Australia. Methods: 11,898 lung cancers, diagnosed during 1982-2000, were analysed to determine age‐adjusted incidence rates by sex, diagnostic epoch, and histological type, and changes in histological distribution at diagnosis. Results: The age‐adjusted incidence of squamous cell carcinoma reduced by 47.1% in males between 1982-86 and 1997-2000, with larger reductions applying to younger age groups. A 34.1% reduction also occurred for small cell lesions in males, whereas a 55.6% incidence increase applied for large cell lesions, and in the age range of 70 years and over, a 29.9% incidence increase for adenocarcinomas. Larger increases were observed for adenocarcinomas and large cell lesions in females. There was also a 48.0% incidence increase in squamous cell carcinomas in females aged 70 years or more. In general, adverse incidence trends were less pronounced and favourable trends more pronounced in the younger age groups of both sexes. Conclusions: The more favourable incidence trends by histology in younger age groups are a positive sign that hopefully will prove to be cohort effects that extend to older ages. Incidence trends have led to an increased proportion among diagnosed cancers of adenocarcinomas and large cell lesions, but this is unlikely to have more than a marginal effect on overall survivals and treatment requirements.